Investigation of the Therapeutic Effect of Doxorubicin Combined With Focused Shockwave on Glioblastoma - Liao, Wei-Hao; Hsiao, Ming-Yen; Kung, Yi; Huang, Abel Po-Hao; Chen, Wen-Shiang (Frontiers in Oncology, 2021)
Background: Glioblastoma multiforme (GBM) is currently the most devastating brain tumor globally and produces a high mortality rate. GBM is also challenging to eradicate using surgery due to its invasive characteristics. Moreover, the blood-brain barrier (BBB) increases the difficulty of transporting most therapeutic drugs to tumor sites. The use of transcranial focused ultrasound (FUS) has recently been investigated for opening the BBB to facilitate drug delivery. A special form of FUS, the shockwave (SW), has also been shown to open BBB efficiently. SW has several advantages including no heating effect, less reactive oxygen species production, good transcranial ability, and no need to supply microbubbles. Methods: We employed a commercial SW device, which is a common tool used for musculoskeletal disorders, to improve doxorubicin delivery across the BBB and evaluated its therapeutic efficacy on GBM rat models. SW emits relatively short but stronger mechanical pulses comparing with FUS. Results: The results demonstrated that doxorubicin combined with SW treatment substantially inhibited tumor growth and prolonged overall survival. Conclusions: The present study shows the non-invasive transcranial SW may have potential for the treatment of GBM in future clinical setting.